A-WEFI Kenya Aquaculture Value Chain Data - Adam, Rahma (2024)
The datasets contain aquaculture value chain data collected from fish input suppliers, fish traders and fish farmers in Kenya. The dataset is mainly women’s empowerment based, but also includes a HN (nutrition module)